2016
DOI: 10.1038/labinvest.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-2, 3-sialyltransferases regulate the multidrug resistance of chronic myeloid leukemia through miR-4701-5p targeting ST3GAL1

Abstract: The aberrant sialylation profile on the surface of leukemia cells has been recognized for its potential diagnostic value towards assessing leukemia multidrug resistance (MDR). MicroRNAs as endogenous regulators of gene expression have been implicated in treating MDR. In this study, we describe the differential expressional profiles of α-2, 3-sialyltransferases (ST) and miR-4701-5p in three pairs of chronic myeloid leukemia (CML) cell lines and 48 clinical samples of bone marrow mononuclear cells from CML patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Therefore, chemoresistance seems to reflect the level of ST3GAL1 expression in the different cell lines as it is doubtful that an untreated cell line could acquire resistance to cytotoxic drugs. A study on the role of α2,3-sialyltransferases on chemoresistance in chronic myeloid leukemia cell lines, also found that a multidrug-resistant phenotype was associated with the altered expression level of ST3GAL1 34 . Moreover, when the expression of ST3GAL1 was downregulated, sensitivity to adriamycin, paclitaxel, and vincristine increased.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, chemoresistance seems to reflect the level of ST3GAL1 expression in the different cell lines as it is doubtful that an untreated cell line could acquire resistance to cytotoxic drugs. A study on the role of α2,3-sialyltransferases on chemoresistance in chronic myeloid leukemia cell lines, also found that a multidrug-resistant phenotype was associated with the altered expression level of ST3GAL1 34 . Moreover, when the expression of ST3GAL1 was downregulated, sensitivity to adriamycin, paclitaxel, and vincristine increased.…”
Section: Discussionmentioning
confidence: 91%
“…Human sialyltransferases are known to be upregulated in several cancers and are also associated with chemoresistance 32 34 . In the present study, we found that ST3GAL1 was upregulated in ovarian cancer tissues and ovarian cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…After data analyses, a total of 26 miRNAs, 248 mRNAs, 1118 lncRNAs, and 382 circRNAs were differential between miR‐145‐5p mimics and NC groups. We noted both tumor suppressive and oncogenic miRNAs were included in the differentially expressed miRNAs, among which miR‐148b‐3p, miR‐150‐3p, miR‐2116‐3p, miR‐3940‐5p, miR‐4653‐3p, miR‐4701‐5p, miR‐4741, miR‐4749‐3p, miR‐4769‐3p, and miR‐663a are tumor suppressive miRNAs . Moreover, miR‐1539, miR‐1825, miR‐3151‐3p, miR‐550a‐3p, miR‐550a‐5p, and miR‐575 are oncogenic miRNAs .…”
Section: Discussionmentioning
confidence: 95%
“…High expression of ST3Gal1 is associated with advanced stage epithelial ovarian cancer (Wen et al, 2017). Altered levels of ST3GAL1 correspond to the drugresistant phenotype of chronic myeloid leukemia (CML) cell lines (Li et al, 2016). However, similar studies of the role of ST3Gal1 in RCC are rare.…”
Section: Discussionmentioning
confidence: 99%